Exploring Students’ Thinking Skills through Motivational Video-Based Learning on Systems of Two-Variable Linear Equations - Jihan Anisah Zahra; Sellen Venita Aurelia; Nonik Indrawatiningsih (Journal of the Indonesian Mathematics Education Society, 2025)
This study aims to exploring how motivational videos can enhance students' mathematical thinking skills. The research employed a qualitative exploratory descriptive method involving eighth-grade students at one state junior high school in Surabaya who were selected based on high pretest scores. The students were given a motivational video designed to present the concept of Systems of Linear Equations of Two Variables through real-life applications and visual explanations. Data collection was conducted through pretest and posttest tasks and analyzed using document analysis techniques to observe students’ development in forming mathematical models, selecting appropriate strategies (substitution and elimination), and drawing logical conclusions. The results showed significant improvements in students' problem-solving abilities, conceptual understanding, and confidence in applying systematic procedures. Qualitative changes were also evident in their metacognitive behaviors, such as planning and evaluating solution steps. In addition, the videos reduced students' anxiety towards mathematics and increased their motivation to learn. These findings indicate that motivational videos, when designed pedagogically and contextually, can effectively support the development of higher-order thinking skills in mathematics learning. The study suggests that teachers integrate digital media into classroom instruction to foster deeper cognitive engagement. Although limited to two subjects, this research provides important insights and encourages further studies with broader samples to evaluate the long-term impact of video-based learning on student thinking development.